The economics of psychedelic-assisted therapies: A research agenda - Marseille, Elliot; Bertozzi, Stefano; Kahn, James G. (Frontiers in Psychiatry, 2022)
After a long hiatus, psychiatry is undergoing a resurgence of interest in psychedelic drugs as therapy for a wide range of mental health disorders Accumulating clinical evidence suggests substantial potential for psychedelics used in a therapeutic context, as treatment for, among other disorders, depression, PTSD, and addictions to tobacco, opioids and alcohol. As soon as 2023, powerful new therapeutic modalities could become available for individuals with mental health problems refractory to traditional therapies. Yet research has lagged on economic considerations, such as costs and cost-effectiveness, the economic effects of widespread implementation, pricing, and methodological considerations relevant to psychedelic therapies. These issues are critical if psychedelic therapies are to become widely accessible. We describe six types of economic analysis and their rationale for decisions and planning including the needs of health care payers. We also outline desirable features of this research, including scientific rigor, long horizon, equity, and a global view.